2022
DOI: 10.1002/cbdv.202200441
|View full text |Cite
|
Sign up to set email alerts
|

Fungistatic Films Containing Cinnamon Essential Oil: New Coatings to Preserve the Nutraceutical Content of Avocado Fruit against Fusariosis

Abstract: Avocadoes are a rich source of nutrients and nutraceuticals that preserve human health. Nevertheless, this fruit is susceptible to phytopathogen infection during the postharvest period causing severe economic losses. Herein, we report on the in situ antifungal assessment of biodegradable films impregnated with the essential oil of Cinnamomum verum (CvEO) as natural fungistatic coatings to extend postharvest quality of Hass avocadoes (Persea americana cv. Hass). These coatings were evaluated on fruits previousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(22 citation statements)
references
References 29 publications
(99 reference statements)
1
21
0
Order By: Relevance
“…For CS@PLA MB, the characteristic peaks of CS appear at 1642 cm –1 belonging to C–O (amido bond I) and 1538 cm –1 belonging to N–H (amido bond II) . In the spectra of CEO/CS@PLA MB with different CEO contents, the peaks at 2926 and 2853 cm –1 reflect the stretching vibration of the C–H and –CH 2 in CEO. , The peaks at 1677 and 1625 cm –1 correspond to the stretching vibration of CO and C–C of CIN in CEO, respectively. Moreover, the obvious peaks at 754 and 691 cm –1 are attributed to the stretching vibration of benzene ring and C–H in olefin of CEO. , With the increasing of the CEO content, the characteristic peaks belonging to CEO strengthen.…”
Section: Resultsmentioning
confidence: 99%
“…For CS@PLA MB, the characteristic peaks of CS appear at 1642 cm –1 belonging to C–O (amido bond I) and 1538 cm –1 belonging to N–H (amido bond II) . In the spectra of CEO/CS@PLA MB with different CEO contents, the peaks at 2926 and 2853 cm –1 reflect the stretching vibration of the C–H and –CH 2 in CEO. , The peaks at 1677 and 1625 cm –1 correspond to the stretching vibration of CO and C–C of CIN in CEO, respectively. Moreover, the obvious peaks at 754 and 691 cm –1 are attributed to the stretching vibration of benzene ring and C–H in olefin of CEO. , With the increasing of the CEO content, the characteristic peaks belonging to CEO strengthen.…”
Section: Resultsmentioning
confidence: 99%
“…[5] Based on the latter points, recent efforts have focused on applying fungistatic films made with chitosan and essential oils as biodegradable/edible coatings for controlling pathogens linked to fruit decay during the postharvest period. [10][11][12][13][14] Previous studies sustain that hybrid films containing chitosan impregnated with essential oils, efficiently regulate the standard growth of Fusarium verticillioides, F. solani, and Clonostachys rosea in avocado fruit. In addition, the in situ growth of Rhizopus stolonifer and Fusarium oxysporum in peaches and cherry tomatoes was effectively delayed.…”
Section: Introductionmentioning
confidence: 93%
“…Interestingly, the malleability of these composites was kept as that of other hybrid films used for the control of phytopathogenic fungi in avocado, tomato, and peach. [10][11][12][13][14] Previous works reported the use of four concentrations of bioactive essential oil in films to prevent the in situ growth of Fusarium verticillioides, F. solani, F. oxysporum, Clonostachys rosea, and Rhizopus stolonifer. The same investigations revealed that concentrations below 0.5 % w/v are ineffective for control- ling these phytopathogens.…”
Section: Physicochemical Properties Of Hybrid Films Containing Lgeo A...mentioning
confidence: 99%
See 2 more Smart Citations